#aquareladudi: interview with Dudi Maia Rosa (Revista Apotheke, 2022)
It is an interview with Dudi Maia Rosa (São Paulo, 1946) about his consistent production of watercolour paintings throughout his career. Dudi Maia Rosa reflects on the intimate, liberating and autobiographical aspects of this technique in his artistic practice.
Keywords: watercolour painting; contemporary art; Dudi Maia Rosa